Black list [compact disc, unabridged] : a thriller - Thor, Brad (Thor, Brad. Scot Harvath., 2012)
Counter-terrorism expert Scot Harvath's name has been added to the Black List, a secret government hit list that only the president of the United States has final approval over. Now, with secret operatives on his trail and a mark on his head, Scot has to find out who framed him, and why, all while trying to stop the deadliest terrorist attack the United States has ever seen.